Effective Factors Influencing the Intention to Use Citizens Complaint Handling System - Nur Shabrina Meutia; Apol Pribadi Subriadi (Journal of Computer Science and Informatics Engineering (J-Cosine), 2021)
The citizen's complaint handling system aims to make citizens easily file a complaint against the condition and development of the city so that it can be followed up immediately, but the implementation of this Smart City program is less than optimal. The real condition shows that there are still many citizens who have not used this application. This study aims to evaluate what factors influence the citizen's intention to use the complaint handling application. The methodology used in this study is a qualitative method with a phenomenological approach. This study conducted in-depth interviews with six research informants, then the results of the interviews were tested and analyzed, and the interview data was encoded. The results of this study found factors that influence the intention to use complaint handling applications. These factors are citizen awareness, social influence, perceived usefulness, and trust. The expected result is a new model that can be implemented to improve the use of complaint handling applications and similar e-government services.